Enhancing System Lifecycle Processes by Integrating Functional Safety Information from Practice into Design Requirements. (31st October 2013) - Lintala, Marja; Ovtcharova, Jivka
To be able to find answers for challenging research questions about the universe, advanced machinery in major research institutions - e.g. accelerator complexes - is needed. In such expensive research facilities, which generate ionizing radiation, it is necessary to protect people, infrastructure and the environment from harm. To meet functional safety requirements, machinery shall fulfil high safety standards throughout its life. This paper aims to propose a methodology for preserving the functional safety of the equipment already in operation and the maintenance phase of the lifecycle. A methodology is proposed to enable better integration of information from practice into design requirements for modifications, such as upgrades and retrofits. The method is based on existing functional safety standards. The goal is to increase the operational time while preserving performance at the intended level.